2021
DOI: 10.1007/s11695-021-05644-y
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Postoperative High Flow Nasal Oxygen Versus Conventional Oxygen Therapy in Obese Patients Undergoing Bariatric Surgery (OXYBAR Study): a Pilot Randomised Controlled Trial

Abstract: NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The proportion of patients with obstructive sleep apnea (OSA) was between 12.5 and 72.5% in five trials 23 27 , while five studies did not provide this information 28 32 . Of the ten studies, two assessed the beneficial effects of HFNO on postoperative pulmonary parameters in patients receiving laparoscopic bariatric surgery 23 , 24 , while eight studies evaluated the efficacy of HFNO against peri-procedural hypoxemia or oxygenation status during anesthesia induction (six trials) 26 – 30 , 32 , tracheal intubation in the intensive care unit (one trial) 31 , and colonoscopy under deep sedation (one trial) 25 . In the HFNO groups, the flow rate ranged from 50 to 120 L/min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of patients with obstructive sleep apnea (OSA) was between 12.5 and 72.5% in five trials 23 27 , while five studies did not provide this information 28 32 . Of the ten studies, two assessed the beneficial effects of HFNO on postoperative pulmonary parameters in patients receiving laparoscopic bariatric surgery 23 , 24 , while eight studies evaluated the efficacy of HFNO against peri-procedural hypoxemia or oxygenation status during anesthesia induction (six trials) 26 – 30 , 32 , tracheal intubation in the intensive care unit (one trial) 31 , and colonoscopy under deep sedation (one trial) 25 . In the HFNO groups, the flow rate ranged from 50 to 120 L/min.…”
Section: Resultsmentioning
confidence: 99%
“…In the HFNO groups, the flow rate ranged from 50 to 120 L/min. In the control groups receiving COT/NIV, mask oxygenation was adopted in four studies 23 , 24 , 27 , 29 , while NIV and nasal cannula oxygenation were used in other four 26 , 30 – 32 and two 25 , 28 RCTs, respectively.
Figure 1 PRISMA flow diagram of study selection for the current meta-analysis.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of HFNO after tracheal extubation was demonstrated to prevent hypoxemia among obese patients following bariatric surgery in one study [ 40 ] but not another. [ 41 ] In propofol sedation for colonoscopy, the desaturation rate was similar between HFNO and standard nasal cannula. [ 42 ] These disagreements may come from the discrepancies in the oxygenation protocol and study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The greater risk of oxygen desaturation in obese patients warrants further development of pre-oxygenation techniques for anesthesia care. However, it remains inconclusive whether HFNO is superior to FMO in preventing perioperative desaturation in obese patients [8,15,16,22,40–42] . Heinrich et al [8] reported that HFNO for 3 minutes generated the highest PaO 2 compared with oxygen insufflation or continuous positive airway pressure via a facemask.…”
Section: Discussionmentioning
confidence: 99%